GP56 Severe hypercalcemic crisis in an infant with idiopathic infantile hypercalcemia caused by mutation in CYP24A1 gene. (June 2019) - Rácz, Orsolya-Adrienn; Emma, Francesco; Konrad, Martin; Fufezan, Otilia; Bulată, Bogdan; Bungardi, Adriana; Căinap, Simona
Abstract : Introduction: The presence of CYP24A1 mutations explains the increased sensitivity to vitamin D in patients with idiopathic infantile hypercalcemia and is a genetic risk factor for the development of symptomatic hypercalcemia that may be triggered by vitamin D prophylaxis in otherwise apparently healthy infants. Case report: We present a case of a 4-month old girl who was initially hospitalized for severe hypotonia, lethargy and failure to thrive. The patient's history revealed recurrent vomiting. On the clinical examination we also noted a high forehead, a high arched palate and short metacarpal bones. Blood tests showed hypercalcemia, low PTH and phosphate and high vitamin D levels. Renal ultrasound showed medullary nephrocalcinosis. Correlating the clinical examination with the blood work vitamin D intoxication, hyperparathyroidism and Jansen's metaphyseal dysplasia were considered and ruled out. Genetic testing was performed and a compound heterozygote state was identified (mutations p.E143del and p.R396W) confirming the diagnosis of idiopathic infantile hypercalcemia. Both mutations have been formerly identified as loss-of-function mutations in the vitamin D-24-hydroxylase gene. Rehydration and furosemide therapy was applied and resulted in the normalization of calcium values and clinical improvement. On the long term the patient followed a low calcium diet and vitamin D supplementation was discontinued. Conclusion: Clinical symptoms, such as failure to thrive, vomiting, increased thirst, anorexia, hypotonia should always bring in discussion the possibility of hypercalcemia in order to diagnose and treat idiopathic infantile hypercalcemia early and also to prevent long-term complications.